1992
DOI: 10.1007/bf02389632
|View full text |Cite
|
Sign up to set email alerts
|

A controlled study of maternal serum concentrations of lipoproteins in pregnancy-induced hypertension

Abstract: Seventeen women with pregnancy-induced hypertension (PIH) and 17 controls with uncomplicated pregnancy who were matched for maternal and gestational age were investigated for lipid concentrations in whole serum and lipoprotein fractions. The triglyceride level in the low-density lipoprotein fraction was higher in PIH patients than in controls (P < 0.03). The differences between values of other parameters did not attain the level of statistical significance, although the tendency of the results was consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 10 publications
2
9
1
Order By: Relevance
“…Normal human pregnancy results in a pronounced physiologic hyperlipidemia involving a gestational rise in blood triglyceride and cholesterol levels. Women with preeclampsia display additional increases in blood lipids, reflecting abnormal lipid and lipoprotein metabolism (18,(1)(2)(3)(4)(5)(6)(7)(8)(9). Leventzen et al (19) analyzed sera obtained from women in late pregnancy after 8-10 hours of fasting and found that serum triglyceride and fatty acid concentrations in women with preeclampsia were higher than those in women with uncomplicated pregnancy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Normal human pregnancy results in a pronounced physiologic hyperlipidemia involving a gestational rise in blood triglyceride and cholesterol levels. Women with preeclampsia display additional increases in blood lipids, reflecting abnormal lipid and lipoprotein metabolism (18,(1)(2)(3)(4)(5)(6)(7)(8)(9). Leventzen et al (19) analyzed sera obtained from women in late pregnancy after 8-10 hours of fasting and found that serum triglyceride and fatty acid concentrations in women with preeclampsia were higher than those in women with uncomplicated pregnancy.…”
Section: Discussionmentioning
confidence: 97%
“…There is evidence that oxidative stress occurs in these disorders, and it has been hypothesized that reactive oxygen species or their metabolites ultimately comprise "defensive" vasodilatory, antiaggregatory, and barrier functioning of the vascular endothelium. Pregnancy in general, and preeclamptic pregnancy in particular, is associated with a marked hyperlipidemia (1)(2)(3)(4)(5)(6)(7)(8)(9). It has been suggested elsewhere that preeclampsia resembles atherosclerotic diseases, wherein hyperlipidemia induces endothelial dysfunction, as occurs in preeclampsia (10).…”
Section: Introductionmentioning
confidence: 98%
“…Most of these studies were conducted in European countries and in the United States of America. Most case-control studies have shown a dyslipidemic pattern in pre-eclampsia patients (Franz & Wendler, 1992;Hubel et al, 1996;Lorentzen et al, 1995;Ogura et al, 2002;Roberts et al, 2003;Ware-Jauregui et al, 1999). These inferences are limited by the fact that the serum lipid levels were analysed in late pregnancy or postpartum, after establishing the diagnosis of pre-eclampsia, whereas the results of prospective cohort studies were not consistent.…”
Section: Introductionmentioning
confidence: 87%
“…12,14 Some 6,10,15 although not all 12,16 previous studies have indicated particularly adverse lipid profiles among women with PIH. Significantly lower levels of HDL2 cholesterol, 6 and significantly higher levels of triglyceride 6,10,15 have previously been reported among women with established proteinuric 6,10,15 or nonproteinuric 6 PIH.…”
Section: Discussionmentioning
confidence: 99%